MULTIMEDIA-BASED ACTIVITY IN YOUNG LEARNERS’ ENGLISH CLASS: IMPLEMENTATION AND OUTCOME - Ida Zuraida Supri (University of Kuningan, 2015)
Abstract: This research aims at investigating how multimedia facilitates young learners’ learning English. The study utilized a descriptive method. This comprised observing, collecting data, classifying data, and analyzing data. Observation to the multimedia is carried out to seek for steps of lessons and the steps are facilitating young learners leaning. The subjects in this study were series of multimedia programs. The results showed that the multimedia programs have presented to five young learners’ learning traits in designing the lessons. Those traits were transferred in terms of activities presented into stages, time allotment/duration, having specific topic, providing songs and funny cartoon characters and scenes, and materials recycling in the lessons. Thus, it can be concluded that the use of multimedia program is beneficial and recommended either in a classroom as a supplementary activity, at home for home learning or watch for fun.Keywords: multimedia, young learners, learning traits